Antibacterial Activities of Biosynthesized Zinc Oxide Nanoparticles and Silver-Zinc Oxide Nanocomposites using Camellia Sinensis Leaf Extract - Jha, Pankaj Kumar; Chawengkijwanich, Chamorn; Pokum, Chonlada; Soisan, Pichai; Techato, Kuaanan (Trends in Sciences, 2023)
Green route of nanomaterials synthesis is increasing in demand due to ecofriendly to the environment. In this research, objective is to biosynthesize and evaluate the antibacterial performance of pure ZnO and Ag/ZnO nanocomposites using Camellia sinensis leaf extracts. Pure ZnO nanoparticles and Ag/ZnO nanocomposites were synthesized using Camellia sinensis leaf extract. The antibacterial effectiveness against gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) bacteria were examined and compared with 1 % Chlorox as a commercial disinfectant by well diffusion method based on the zone of inhibition. Pure ZnO nanoparticles and Ag/ZnO nanocomposites had hexagonal shape ZnO nanoparticles and rectangular shape Ag nanoparticles in Ag/ZnO nanocomposites with a particle crystal size between 20 - 30 nm with carboxylic and phenolic functional group attached on it. Ag/ZnO nanocomposites exhibited antibacterial effectiveness against both gram-positive and gram-negative bacteria, while pure ZnO nanoparticles exhibited antibacterial effectiveness against only gram-positive bacteria. Conversely, 1 % Chlorox and 1 % DMSO showed no significant antibacterial activity against gram-positive and gram-negative bacteria. Camellia sinensis mediated ZnO and Ag/ZnO nanoparticles showed antibacterial potential against S. aureus and E. coli suggesting that green route to synthesis of antibacterial nanoparticles can be an excellent strategy to develop eco-friendly disinfectant products HIGHLIGHTS Zinc oxide nanocomposites biosynthesis by Camellia sinensis at low pH, Antibacterial properties of ZnO nanoparticles and Ag/ZnO nanocomposites on Escherichia coli ATCC 8739 and Staphylococcus aureus ATCC 6538P strains, Disinfection application. GRAPHICAL ABSTRACT